2011
DOI: 10.1016/j.jconrel.2011.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid: Evaluation as a potential delivery vehicle for vitronectin:growth factor complexes in wound healing applications

Abstract: We have previously reported that novel vitronectin:growth factor (VN:GF) complexes significantly increase re-epithelialization in a porcine deep dermal partial-thickness burn model. However, the potential exists to further enhance the healing response through combination with an appropriate delivery vehicle which facilitates sustained local release and reduced doses of VN:GF complexes. Hyaluronic acid (HA), an abundant constituent of the interstitium, is known to function as a reservoir for growth factors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 67 publications
0
40
0
Order By: Relevance
“…VN: GF was reported to significantly increase re-epithelialization in a porcine deep dermal partial-thickness burn model (Upton et al, 2008). Despite the advantages of HA in wound healing, results obtained from this study (Xie et al, 2011) indicated that, there was no significant difference between the thicknesses of the epidermis treated with VN:GF complexes alone and VN:GF complexes together with HA. Therefore, promising use of HA in burn healing process still needs a step of skin penetration enhancement (El-Refaie et al, 2015).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…VN: GF was reported to significantly increase re-epithelialization in a porcine deep dermal partial-thickness burn model (Upton et al, 2008). Despite the advantages of HA in wound healing, results obtained from this study (Xie et al, 2011) indicated that, there was no significant difference between the thicknesses of the epidermis treated with VN:GF complexes alone and VN:GF complexes together with HA. Therefore, promising use of HA in burn healing process still needs a step of skin penetration enhancement (El-Refaie et al, 2015).…”
Section: Introductionmentioning
confidence: 52%
“…This long time might also result in impaired healing. Recently, the potential of HA as a suitable delivery vehicle to facilitate sustained local release and reduced doses of VN:GF (vitronectin:growth factor) was investigated (Xie et al, 2011). VN: GF was reported to significantly increase re-epithelialization in a porcine deep dermal partial-thickness burn model (Upton et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that the local concentration of EGF needs to be sufficiently high and prolonged for effective wound healing [126,132,133]. Therefore, different drug delivery systems that are able to protect and stabilize the protein have been investigated, including hydrogels, sponges, polymeric pellets, nanofibers, microspheres, a biomimetic delivery system that incorporated EGF with biocompatible components such as hyaluronic acid, collagen, vitronectin or liposome, and more recently, a poloxamer gel formulation of recombinant low-molecular-weight protamine conjugated EGF (rLMWP-EGF) by conjugating a highly positively charged rLMWP to the N-terminal of EGF [134140]. The latter has shown better healing effects on burn injuries [139].…”
Section: Egf Clinical Relevancementioning
confidence: 99%
“…In their first pre-clinical evaluation, vitronectin complexes of IGFs and EGF accelerated healing of partial-thickness burn wounds in pigs, although this approach did require multiple administrations per week [108]. To improve the clinical usefulness, HA was then added as a carrier system for vitronectin:GF complexes [109]. In a clinical pilot study, this therapy demonstrated convincing efficacy at re-epithelializing venous leg ulcers, and also showed promise for treating other types of chronic wounds [110].…”
Section: Complexes and Conjugatesmentioning
confidence: 99%